26th Annual GP2A Medicinal Chemistry Conference & 32nd Journées Franco-Belges de Pharmacochimie - Patrick Dallemagne; Christophe Rochais; Pascal Marchand; Thierry Besson (MDPI AG, 2019)
As a joint meeting, the 26th Medicinal Chemistry Conference of GP2A and 32nd Journées Franco-Belges de Pharmacochimie took place between 13th and 15th June at Asnelles sur Mer (Normandie, France), providing a unique opportunity for a wide group of European medicinal chemists to engage. Topics included chemical tools for medicinal chemistry, protein-protein interactions, epigenetics, natural product-inspired molecules, computer-aided drug design, and new strategies for the design and development of drugs. Abstracts of invited lectures, proffered young researcher communications, flash communications and posters presented during the meeting are collected in this report.